Design and Simulation of 3D Micromixer with Planar Microchannel - Abd Razak, Muhammad Saidi; Abdul Hamid, Intan Sue Liana (Evolution in Electrical and Electronic Engineering, 2022)
Active and passive micromixers are the two types of micromixers. Passive micromixers will be the focus of this study due to their easy manufacturing procedures and quick implementation in a complex microfluidic environment. The passive micromixer is the safest kind of fluid mixing because of the laminar flow (Reynold number 1). For performance mixing, passive micromixers frequently rely on channel geometry. Based on the basic planar model micromixer baseline performance, three different micromixers were tested in this study. The micromixers are basic planar T- shaped micromixer in the first optimized design. Concept of planar B-spline and Tesla with a grooved meandering surface with obstacle inside the channel is the second and third optimized design. These micromixers have a 40 mm channel length, 10000 μm inlet length, and 600 μm m and 100 μm width and depth, respectively. To analyze the mixing performance of each planar micromixer design, the inlet flow rate is set at 0.07m/s and the two solutions are set at concentrations of 30 mol/m3 and 20 mol/m3. Planar B-spline micromixer design with obstacle inside the channel is analyzed to be as the better implementation on the basic planar micromixer as it has complete the mixing value of the standard deviation of concentration at the end of the mixing channel when compared to the basic planar micromixer, the standard deviation of planar B-spline micromixer is observed to be at the lowest value and mixing faster when compared to the standard deviation of the other planar micromixer design.